Performance Analysis of Wi-Fi Wireless Networks In A Vortex Media Access And Reseller Broadband - Ferdyno Kalumbang; Ahmad Faix Farisky; Tito Sumarsono; Solehatin Solehatin (SHM Publisher, 2023)
The research aims to analyze network performance in an office and also a broadband reseller, to determine network quality through monitoring trials on servers and clients. The research uses data collection methods by conducting interviews. The second stage is needs analysis as a benchmark for network performance analysis. The next stage is monitoring the server and client to determine network speed. From research that has been carried out related to the analysis of WiFi wireless networks in small and medium office environments using custom network topology to suit needs, as well as broadband resellers also using custom network topology. The distribution of bandwidth from each place adjusts to their respective needs to get quality network connections The good thing is, that there are no specific standards for dividing bandwidth, it all depends on needs. The results of the data obtained from the analysis of the two places, of course from the analysis that the author has carried out, we can know the quality of the network connection from the two places, apart from that the topology design used by the office environment and also broadband resellers can increase knowledge about WiFi wireless networks and can be an example to open a business in the field of WiFi wireless networks that can provide faster WiFi performance with wider coverage.